Harnessing Floriculture Potential of Northeastern India - Rampal; Prasad, K V (Indian Horticulture, 2024)
Genetic resources of Northeast are depleting very fast. They need to be conserved and protected from biopiracy, while at the same time, they need to be used wisely for commercial purposes. In a globalised economy where trade barriers are being relaxed, it is obvious that orchids and exotic flowers from other countries will dominate our markets and it is necessary to protect the interests of our growers. We need to find ways and means to secure our markets against competing countries and to exploit the potential for export markets. In addition, new centres of consumption are emerging in South East Asia, the Middle East and Eastern Europe. The scenario offers the opportunity to capitalise on strengths and turn weaknesses into opportunities. However, in the consumer-oriented market, the quality of the product and the delivery system will play an important role. Marketing is no longer a meeting of buyers and sellers, but a complex process determined by the quantity of products and the reliability of delivery. With the help of IT, there is likelyto be a new distribution structure, which will be a virtual market requiring demand, branding, cataloguing and quality assurance.